Processing and Analysis of ASTER and Landsat 8 Scenes to Aid in Geological Mapping: A Case Study of Murchison Greenstone Belt Area, South Africa - Thomas, Abraham (Geomatics and Environmental Engineering, 2020)
This paper presents processing and analysis results of ASTER and Landsat 8 scenes to aid in geological mapping of Murchison Greenstone Belt region of Limpopo Province, South Africa. Images of ASTER acquired in 2005 and 2006 and Landsat 8 acquired in 2019 were downloaded and subset covering 5 mapping sheets was extracted. Images of different band ratios and band combinations were experimented using ENVI and SNAP software to identify suitable band/band ratio combinations to produce FCCs that enabled discrimination of lithology, structural features, lineaments, alteration and iron oxides, land/water, surface features, vegetation cover and healthy vegetation etc. Using DEM data, slope and shaded relief were also prepared that enabled the identification of the extent of protruded outcrops, some structural features and lineaments using different FCC displays. These datasets prepared in ENVI file format were later exported to GeoTiff/Imagine file for display in ArcMap by the mapping geologists. FCCs made in various band combinations, ratio combination and also with slope are useful in discriminating geology, structural features and protruded outcrops including dykes that are not so visible in a true colour image of the same resolution. This study could illustrate the usefulness of remote sensing analysis to aid in geological mapping using freely available ASTER and Landsat 8 data.